Interacting Genomic Landscapes of REC8-Cohesin, Chromatin, and Meiotic Recombination in Arabidopsis. Issue 4 (5th February 2020) - Lambing, Christophe; Tock, Andrew J.; Topp, Stephanie D.; Choi, Kyuha; Kuo, Pallas C.; Zhao, Xiaohui; Osman, Kim; Higgins, James D.; Franklin, F. Chris H.; Henderson, Ian R.
Abstract : REC8 association with the genome correlates with multiple chromatin states and is required to organize meiotic chromosome architecture and interhomolog recombination. Abstract: Meiosis recombines genetic variation and influences eukaryote genome evolution. During meiosis, DNA double-strand breaks (DSBs) enter interhomolog repair to yield crossovers and noncrossovers. DSB repair occurs as replicated sister chromatids are connected to a polymerized axis. Cohesin rings containing the REC8 kleisin subunit bind sister chromatids and anchor chromosomes to the axis. Here, we report the genomic landscape of REC8 using chromatin immunoprecipitation sequencing (ChIP-seq) in Arabidopsis ( Arabidopsis thaliana ). REC8 associates with regions of high nucleosome occupancy in multiple chromatin states, including histone methylation at H3K4 (expressed genes), H3K27 (silent genes), and H3K9 (silent transposons). REC8 enrichment is associated with suppression of meiotic DSBs and crossovers at the chromosome and fine scales. As REC8 enrichment is greatest in transposon-dense heterochromatin, we repeated ChIP-seq in kyp suvh5 suvh6 H3K9me2 mutants. Surprisingly, REC8 enrichment is maintained in kyp suvh5 suvh6 heterochromatin and no defects in centromeric cohesion were observed. REC8 occupancy within genes anti-correlates with transcription and is reduced in COPIA transposons that reactivate expression in kyp suvh5 suvh6 . Abnormal axis structures form in rec8 that recruit DSB-associated protein foci and undergo synapsis, which is followed by chromosome fragmentation. Therefore, REC8 occupancy correlates with multiple chromatin states and is required to organize meiotic chromosome architecture and interhomolog recombination.